DESKRIPSI POLA SALURAN TATANIAGA PALA (Myristica fraggan haitt) DI KENAGARIAN TANJUNG SANI KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Analia, Devi; Fairuzi, Syofyan; Tanjung, Faidil; Pimura, Ramita Sari (Jurnal AGRISEP, 2015)
The research purpose is to describe nutmeg’s marketing channel pattern and to identity of marketing instutional function that involves in marketing channel. This research was conducted in Juli – Augustus 2015. Location was chosen purposively with a reason that this district has the largest production in West Sumatra. The research method used is survey and descriptive analysis. The survey is doing by following marketing channel pattern that happen and observation activity that doing by farmer as producers to middlemen or finar consumers. The result shows that there are 2 patter of marketing channel in location. First pattern marketing channel : farmers – man in village. Second patter marketing channel : farmers – whole saler. Their activity according to marketing function consist of exhange function(selling and buying), phisic function (transportation, saving, sortation) and fasility (finance, market information, risk management). As important comodity that have contribute to gaverment, this comodity need goverment support to increase selling value and production. By the support it will imcrease farmers revenue.